A grey correlation-based TOPSIS approach for optimization of surface roughness and micro hardness of Nitinol during WEDM operation. (2020) - Das, Partha Protim; Chakraborty, Shankar
Abstract: Shape memory alloys, like Nitinol (NiTi), CuAlTi etc. have drawn attention to a wide range of applications because of the unique ability to memorize their previous shapes. Machining of those materials has become quite challenging with conventional machining processes for which wire electrical discharge machining (WEDM) process is selected. This paper illustrates the application of grey correlation-based technique for order of preference by similarity to ideal solution in obtaining the optimal parametric mix for the said process for better surface roughness along with higher micro hardness. The optimal parametric combination is found as pulse-on time = 10 µs, discharge current = 10 A, wire tension = 12 N, wire speed = 150 mm/s and flushing pressure = 1 bar. The derived parametric condition is validated based on the predicted response values showing significant improvements in all the responses as compared to those attained by the earlier researchers. The analysis of variance results identify discharge current as the most influential process parameter dominating the responses.